Analytical modeling of dielectric modulated negative capacitance MoS2 field effect transistor for next‐generation label‐free biosensor. (25th August 2022) - Panda, Deepak Kumar; Lenka, Trupti Ranjan; Singh, Rajan; Goyal, Vishal; Boukortt, Nour El Islam; Nguyen, Hieu Pham Trung
Abstract: In this paper, a dielectric modulated negative capacitance (NC) MoS2 FET‐based biosensor is proposed for label‐free detection of biomolecules such as enzymes, proteins, DNA, and so forth. Various reports present on experimental demonstration and modeling of NC MoS2 FET but it is never utilized as a dielectric modulated biosensor. So, in this work, the modeling, characterization and sensitivity analysis of dielectric modulated NC MoS2 FET is focused. For immobilization of biomolecules, a nanocavity is formed below the gate by etching some portion of the gate oxide material. The immobilization of biomolecules in the cavity leads to a variation of different electrostatic properties such as surface potential, threshold voltage, drain current, and subthreshold swing which can be utilized as sensing parameters. An analytical model for the proposed biosensor is also developed in the subthreshold region by considering the properties of two‐dimensional ferroelectric materials and benchmarked with TCAD device simulations. The effect of change of gate length and doping concentration on different electrical properties is also analyzed to estimate the optimum value of channel doping. The results prove that the proposed device can be used for next‐generation low power label‐free biosensor which shows enhanced sensitivity as compared to traditional FET‐based biosensors.